BEYOND THE BUZZWORD: WHAT THE LITERATURE SAYS ABOUT CORPORATE SOCIAL RESPONSIBILITY - Faza Wahyu Anggrainy; Sultan Maulana Hakim; Ester Hanna Gunawan; Dian Widiyati (PT. ZILLZELL MEDIA PRIMA, 2025)
This research aims to examine the influence of tax aggressiveness, firm characteristics, good corporate governance, ownership structure, environmental performance, leverage, board of commissioner's size, and profitability on Corporate Social Responsibility (CSR) in companies listed on the Indonesia Stock Exchange (IDX). This study employs a qualitative approach using the Systematic Literature Review (SLR) method and applies the PRISMA framework in reviewing 15 selected journal articles published between 2013 and 2023. The results indicate that firm characteristics, good corporate governance, environmental performance, board of commissioner's size, and profitability have varying effects on CSR disclosure depending on company context. Meanwhile, tax aggressiveness, leverage, and ownership structure tend to have a negative or inconsistent influence on CSR.